Comparison of the Effectiveness of Rifaximin plus Lactulose versus Lactulose Alone in Overt Hepatic Encephalopathy in Terms of Complete Reversal (Journal of Fatima Jinnah Medical University, 2024)
Background: Hepatic encephalopathy is a serious complication of liver disease, marked by cognitive impairment and potentially life-threatening consequences. Lactulose has long been a standard treatment, but its effectiveness may be limited. Adding rifaximin to lactulose has shown promising results in managing overt hepatic encephalopathy (OHE). This study compared the frequency of complete reversal of encephalopathy by rifaximin plus lactulose versus lactulose alone in patients with OHE.Patients and methods: A randomized controlled trial was carried out at Gastroenterology, DHQ, Gujranwala.  The patients diagnosed with hepatic encephalopathy (age range = 18-60 years) were included. On the contrary, patients with serum creatinine of >1.5 mg/dl at admission, diagnosed with hepatocellular carcinoma, active alcohol intake (
Keywords: Overt Hepatic Encephalopathy; Rifaximin; Lactulose; Reversal of OHE; Model for End-Stage Liver Disease (MELD)